Samuel Henry Eells papers - Eells, Samuel Henry, 1836-1864.
Letters from Eells to his family from camps in Arkansas and Tennessee, where he served as assistant surgeon with the 12th Michigan Infantry Regiment, U.S. Army.
Assistant surgeon with the 12th Michigan Volunteers.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army. -- Michigan Infantry Regiment, 12th (1862-1866); Arkansas -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Medical care; Army officers; Surgeons